Robert Ludlum's The Bourne enigma [compact disc, unabridged] : a new Jason Bourne novel - Lustbader, Eric (Lustbader, Eric. New Jason Bourne novel., 2016)
Bourne must travel to war torn Syria and then Cyprus as he chases the astonishing truth. The clock is ticking, and Bourne has less than four days to solve Karpov's riddle, and hunt down Borz, if he hopes to prevent a cataclysmic international war.